Protocolo de Revisión de Bombas de Infusión - Lejeune, J.; Rodríguez, M. F.; Román, J. R.; Porrón, M. A. (Revista Mexicana de Ingenieria Biomedica, 1999)
Studies have made evident the associated risks of infusion pumps. Their widespread use also creates further technical and economic problems, which can only be solved by their rational use and the implementation of inspection procedures to assure their optimal performance. Statistics on the most frequent problems are presented and a universal infusion pump inspection procedure is proposed to guarantee optimal performance.